Use of Six Sigma methodology for Road construction work (International Journal of Advanced Research in Science, Management and Technology, 2022)
Six Sigma was developed in 1980’s in manufacturing industry & became popular as process improvement method. Although Six Sigma has been implemented in the manufacturing & other services industries, it is still relatively a new concept in the road construction industry. This paper includes the detailed methodology of Six Sigma. The market survey about need of process improvement is done particularly to know concepts of quality, cost, productivity, productivity time, customer satisfaction and use of Six Sigma within road construction industries and a case study on how Six Sigma can be implemented on construction work of a public building to minimize defects and thereby to improve quality of work.Particularly Six Sigma can provide a broader quality concept, detailed performance measurement, coordinated & repeatable performance improvement. Six Sigma is discussable within construction context due to differences of manufacturing & construction industry. Taking everything in consideration, it is obvious that Six Sigma has a lot in order to accelerate fundamental & cultural challenges construction industry needs.
Keywords: Six Sigma, Road Construction Industry, Quality Control, Process improvement, DMAIC, DPMO